Considerations for Size, Surface Charge, Polymer Degradation, Co‐Delivery, and Manufacturability in the Development of Polymeric Particle Vaccines for Infectious Diseases. Issue 3 (18th January 2021) - Genito, Christopher J.; Batty, Cole J.; Bachelder, Eric M.; Ainslie, Kristy M.
Abstract : Vaccines have advanced human health for centuries. To improve upon the efficacy of subunit vaccines they have been formulated into nano/microparticles for infectious diseases. Much progress in the field of polymeric particles for vaccine formulation has been made since the push for a tetanus vaccine in the 1990s. Modulation of particle properties such as size, surface charge, degradation rate, and the co‐delivery of antigen and adjuvant has been used. This review focuses on advances in the understanding of how these properties influence immune responses to injectable polymeric particle vaccines. Consideration is also given to how endotoxin, route of administration, and other factors influence conclusions that can be made. Current manufacturing techniques involved in preserving vaccine efficacy and scale‐up are discussed, as well as those for progressing polymeric particle vaccines toward commercialization. Consideration of all these factors should aid the continued development of efficacious and marketable polymeric particle vaccines. Abstract : Properties such as size, surface charge, degradation rate, and the co‐delivery of antigen and adjuvant all affect the immune responses of polymeric particle vaccines for infectious disease. A review of current and past literature reveals these effects vary with polymer type, antigen, adjuvant, and route of administration. Vaccine manufacturing methods also impact efficacy, scalability, and marketability.